PENGARUH BIAYA PRODUKSI DAN BIAYA OPERASIONAL TERHADAP LABA PERUSAHAAN - Totok Sasongko; Nur Ida Iriani; Eti Ernawati (Unitri Press, 2021)
This study aims to see how much influence production costs and operating costs have on increasing operating profit in the UMKM Lima Sarana Bersih Malang City. This study used quantitative methods through interviews, observation, documentation, and literature study. Test the validity of the data was using validity, normality, multicollinearity, and heteroscedasticity tests, followed by simple and multiple linear regression tests and T test and F test. The results showed that partially production costs and operational costs have a significant and positive effect on increasing operating profit with a t value count 4, 963 and 3,280. Simultaneously, production costs and operational costs also have a significant effect on increasing operating profit with the calculated F value of 45,463 or 97.7%. From these findings, what needs to be considered was that an increase in production costs and operational costs in a controlled and proportional manner will increased operating profit